Propofol dose and efficacy of defibrillation testing during implantation of subcutaneous implantable cardioverter‐defibrillators: A retrospective, single center cohort study. (9th December 2022) - Trolese, Luca; Dall'Aglio, Pietro Bernardo; Steinfurt, Johannes; Gressler, Alexander; Faber, Thomas; Cipriani, Alberto; Migliore, Federico; Westermann, Dirk; Hilgendorf, Ingo; Jäckel, Markus
Abstract: Introduction: Defibrillation testing (DFT) is recommended during subcutaneous implantable cardioverter‐defibrillator (S‐ICD) implantation. Previous studies analyzing the potential interference of propofol with defibrillation threshold are inconsistent. The purpose of this study was to analyze whether propofol affects DFT post S‐ICD placement. Methods: All patients with S‐ICD implantation between 01/2017 and 11/2020 at the University Heart Center Freiburg were retrospectively analyzed. Two groups were generated depending on the success of the first shock during DFT. Implantation characteristics and dose of anesthetics were analyzed. Results: In 12 of the included 80 (15%) patients, first shock during DFT failed. The absolute dose of propofol was significantly higher in patients with first shock failure (median 653 mg [IQR 503–855]) compared to patients with first shock termination (376 mg [200–600]; p = 0.027). Doses of opioids and midazolam as well as type of anesthesia did not differ between the groups. A multivariable binary logistic regression analysis confirmed an independent association of first shock termination and propofol dose (per 100 mg: OR 0.73 (95% CI: 0.56–0.95); p = 0.021). Conclusion: There is an independent association of propofol dose and first shock failure in routine S‐ICD defibrillation testing.